Breastfeeding practices of ethnic minorities in Northern Vietnam: A population-based cross-sectional study (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: Breastfeeding is the most important and essential practice to help children develop comprehensively, physically, mentally, and intellectually. Therefore, this study aimed to explore the breastfeeding practices among ethnic minority mothers with children under two years old in two communities in Muong Nhe district, Dien Bien province of  Northern Vietnam.Materials and methods: This cross-sectional study was conducted on 457 Mong ethnic mothers who had children under two years old in Nam Khe and Muong Toong communes in Muong Nhe district, Dien Bien province,  Northern Vietnam from September 2018 to June 2019. Results: The proportion of children being breastfed was 90.6%, while the percentage of mothers who knew about the benefits of breastfeeding was less than 60.0%. Conclusion: While the proportion of children being breastfed was high, the percentage of mothers who knew about the benefits of breastfeeding was low. The proportion of mothers who practiced correctly was higher than the percentage of those with accurate knowledge of breastfeeding.